Biocomposites of cellulose reinforced starch: improvement of properties by photo-induced crosslinking - Kumar, Annamalai Pratheep; Singh, Raj Pal (Bioresource Technology, 2008)
In the present study, the composite films have been prepared from the aqueous dispersions of starch with microcrystalline cellulose using glycerol as plasticizer and irradiated under ultraviolet (UV) light using sodium benzoate as photo-sensitizer. Photocrosslinking was characterized by measuring the water absorption under 100% relative humidity, swelling degree and gel fraction in dimethylsulphoxide (DMSC), upon irradiation time. Both, the incorporation of cellulose and photo-irradiation were found to decrease the water absorption, swelling in DMSO and increase the gel fraction. Thermal transitions indicated the anti-plasticization of amylopectin chains at the fiber/matrix interface. With increasing content of cellulose and photo-irradiation time, the tensile modulus and strength were found to improve. It is summarized that the combination of cellulose reinforcement and photo-crosslinking of matrix has improved the physical and mechanical properties. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Biocomposites; cellulose; Photo-irradiation and crosslinking; Starch